Financial and Market Decision-Making Tools for Housing Development - Zainal , Rozlin; Hashim, Fazian; Shareh Musa, Sharifah Meryam (International Journal of Sustainable Construction Engineering and Technology, 2021)
Most developers decide intuitively without scientific analysis tools when brainstorming ideas for housing development at the initiation phase. The situation of non-persistence and inconsistent purposes between the main participants in the process, and the specific peculiarities of the speculative housing market continue to be a concern. The paper aims to classify the decision-making tools for housing development at the initiation phase in Malaysia. This research implements the Delphi questionnaire survey method. Data collection involved 50 respondents among Malaysian housing developers. However, only 34 developers contributed to the study in the second round and eventually, 12 developers were left for the last round. Results confirm that the developers in Malaysia favor to make their development speculation decisions depending on modest financial and market past data exclamation and the simple use of numerical tools in generating a primary proposal. These shortcomings are principally attributed to time and economic constraints and the deficiency of financial expertise among the professional team of the developer organisations’.